Prior Sexual Victimization and Rape Myth Acceptance: Direct Victimization, Vicarious Victimization, and Gender - Li, Nan (Victims & offenders, 2026)
Rape myths are widely and persistently held attitudes and beliefs that falsely blame victims for acts of sexual violence and deny accountability of perpetrators. Further, rape myth acceptance is positively associated with perpetration and hinders help-seeking among victims. Given the importance of rape myth acceptance, this study examined the effects of prior direct and vicarious sexual victimization on rape myth acceptance and explored the moderating effect of gender. Data were collected from 1,318 adults aged 18 and older using a web-based survey. Factor analysis identified two underlying constructs associated with rape myth acceptance, victim blameworthiness and denial of responsibility, and both of these constructs were regressed on direct and vicarious sexual victimization, net of controls. Direct experiences of prior sexual victimization, using both behavioral-based definitions and rape acknowledgment, were related to both constructs of RMA. Vicarious experiences of sexual victimization were unrelated to RMA. Further, gender moderated the relationship between direct sexual victimization and RMA, as the positive relationship was only observed among men. The results provide valuable insights into the relationship between prior sexual victimization and rape myth acceptance and highlight important avenues for intervention to minimize rape myth acceptance in society.